The Impact of Technological Limitations on the Adoption of E-Government Applications by Greater Amman Municipality: A Filed Stud - Al-Jabari, Neven (Jordan Journal of Business Administration, 2021)
This study aimed to identify the impact of technological limitations in its various dimensions (communication, integration, software, security and privacy) on the adoption of e-government applications using the (TAM) model by the employees of Greater Amman Municipality. For this purpose, a questionnaire consisting of (36) paragraphs was designed and the simple random sampling method was used to collect data from the study population. The questionnaire was distributed to all individuals working in administrative positions (lower, middle and upper) in Greater Amman Municipality. The total number of questionnaire forms was (400) and (381) responses were retrieved, of which (375) were valid for statistical analysis; i.e., (94%). This study relied on the analytical descriptive approach to collect the data needed to complete it. The statistical software for Social Sciences (SPSS) was used in analyzing the study data and testing the hypotheses. The most important recommendations are: working for overcoming all the technological limitations facing Greater Amman Municipality and preventing the adoption of e-government application to accelerate gains and benefit from e-government application. The study also recommended that Greater Amman Municipality should provide the necessary infrastructure to build a strong electronic government, in addition to the proliferation of Internet, which is one of the basic requirements of building an electronic government. The study also recommended working to solve problems facing institutions, including modernizing old computers, so that workers in institutions can develop programs for the adoption of e-government easily and safely.